2005
DOI: 10.1007/s12055-005-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure changes during cardiopulmonary bypass

Abstract: Background: Ocular complications during cardiopulmonary bypass (CPB) are common, and one reason could be increased intraocular pressure (IOP).Methods: We measured IOP with a Perkins applanation tonometer in 20 patients having elective coronary artery bypass graft surgery with CPB.Results: IOP increased when CPB was started (p <0.001), and was maintained for 20 minutes, with a gradual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Increased IOP may contribute to the higher incidence of ION after operations involving CPB. Sanjay et al showed that intraocular pressure (IOP) increases on commencement of CPB and maximally at 20 minutes to 21 mmHg [ 31 ]. Methods to reduce IOP and therefore maximise intraocular perfusion pressure must be sought, including head position and use of loose endotracheal tube ties.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IOP may contribute to the higher incidence of ION after operations involving CPB. Sanjay et al showed that intraocular pressure (IOP) increases on commencement of CPB and maximally at 20 minutes to 21 mmHg [ 31 ]. Methods to reduce IOP and therefore maximise intraocular perfusion pressure must be sought, including head position and use of loose endotracheal tube ties.…”
Section: Discussionmentioning
confidence: 99%